Cerebral Venous Thrombosis in the Setting of Malignancy: Case Report and Review of the Literature - Constantine N. Logothetis; Charles Pizanis (Case Reports in Hematology)
Cerebral venous thrombosis (CVT) is a rare condition that can be difficult to diagnose due to its vague and nonspecific symptoms. It is even more unusual to identify CVT in association with malignancy. Given the rarity of this disease, treatment and management of CVT in the setting of malignancy is not well defined. This case report and review of the literature addresses the epidemiology, pathophysiology, and medical treatment for malignancy-related CVT.